Analysis of the known methods of channels communication control with the interference and selective fading - Zhyvotovskyi, Ruslan; Momit, Alexander; Onbinskyi, Yaroslav; Lyashenko, Anna (Національний технічний університет "Харківський політехнічний інститут", 2019)
Designing adaptive radio systems, depending on their purpose, solves the problem of optimizing one of the performance indicators with restrictions on others. In turn, the development and implementation of adaptive information sharing techniques require the establishment of effective procedures for monitoring and predicting the status of communication channels and the quality of information transmission. Given the rapid development of electronic warfare facilities, the expansion of the list of interferences that can be created by these complexes, it is great relevance for further scientific research on the creation of new methods of monitoring the status of the communication channel. In this research, the authors analyzed the characteristics of the main methods for assessing the status of communication channels. In the course of the analysis, the authors used general scientific methods of analysis and synthesis, the basic provisions of communication theory, data transfer theory, space-time coding theory, noise immunity theory, signal-code theory, etc. The authors of the article analysis of the known methods of estimating the state of the channel of multi-antenna communication systems showed that the known scientific articles do not contain the following: parallel estimation of the status of the channel by several indicators; obtaining a generalized channel status assessment; continuous evaluation of several characteristics in real-time; at the same time evaluate both the linesdown and the lines up; the combination of the impulse response of the channel state, the frequency response of the channel status, and the bit error probability is not used for the estimation. It is established that at present there is no universal methodof monitoring the status of channels of multi-antenna radio communication systems, which would give an accurate, fast estimate of the status of the channel in real-time, which would allow effective adaptation in a channel with non-stationary parameters.

При проектуванні адаптивних систем радіозв’язку залежно від їх призначення вирішується завдання оптимізації одного з показників ефективності при встановлених обмеженнях на інші. В свою чергу, розробка і впровадження адаптивних методів інформаційного обміну вимагають створення ефективних процедур контролю та прогнозування стану каналів зв’язку і якості передачі інформації. Враховуючи бурхливий розвиток засобів радіоелектронної боротьби, розширення переліку завад, що можуть бути створені зазначеними комплексами, набувають великої актуальності подальші наукові дослідження з питання створення нових методів контролю стану каналу зв’язку. В зазначеному дослідженні авторами був проведений аналіз характеристик основних методів оцінки стану каналів зв’язку. В ході зазначеного аналізу авторами були використані загальнонаукові методи: аналіз та синтез, основні положення теорії зв’язку, теорії передачі даних, теорії просторово-часового кодування, теорії завадостійкості, теорії сигнально-кодових конструкцій та інші. Проведений авторами статті аналіз відомих методів оцінювання стану каналу багатоантенних систем зв’язку показав, що в відомих наукових працях відсутнє наступне: паралельна оцінка стану каналу за декількома показниками; отримання узагальненої оцінки стану каналу; постійне оцінювання декількох характеристик в режимі реального часу; одночасне оцінювання як лінії вниз,так і лінії вгору; для оцінки не використовується поєднання імпульсної характеристики стану каналу, частотної характеристики стану каналу та ймовірності бітової помилки. Встановлено те, що на даний момент не існує універсального методу контролю стану каналів багатоантенних систем радіозв’язку, котрий б давав точну, швидку оцінку стану каналу в реальному часі, мав би можливість ефективної адаптації в каналі з нестаціонарними параметрами.
Аналіз відомих методів контролю стану каналів систем зв’язку з навмисними завадами та селективними завмираннями
Keywords: signal-to-noise ratio; data rate; bit error probability; відношення сигнал/шум; швидкість передачі інформації; ймовірність бітової помилки